The Madden-Julian Oscillation and regional rainfall variability over Sub-Saharan Africa - (:unkn) unknown (My University, 2007)
The role of the Madden-Julian Oscillation ("MJO") on rainfall variability in Sub-Saharan Africa is examined, based on daily rain-gauge records and the NCEP-DOE AMIP-II reanalyses. The convective and dynamical signal associated with the MJO is extracted using two differing methodologies, the BMRC daily indices (Wheeler & Hendon 2004) on the one hand, and a Local Mode Analysis ("LMA", Goulet & Duvel 2000) on the other hand. The temporal variability of the MJO (in terms of period, amplitude, seasonality and location of the convective anomalies) is first analysed. Though the overall amplitude of the signal is not related to El Niño, the oscillations occurring under El Niño (La Niña) conditions tend to be shorter (longer). Surface conditions such as sea surface temperature and the seasonal cycle in the Tropics are two features that play a predominant role on the location of the associated convective clusters. The response of the African rainfall to the MJO is then examined for 3 distinct regional indices. The rainy season(s) is (are) in each case significantly triggered. In Equatorial East Africa Kenya and northern Tanzania) the Highlands show the succession of a dry and a humid phase over the MJO cycle. The associated rain-causing mechanisms mainly involve deep convection. In the eastern plains and on the coast, the peak of rainfall is out-of-phase and results from a strengthening of the trade winds over the Indian basin. A significant influence of the MJO is also detected over Southern Africa (south of 15°S) and depends on an intraseasonal modulation of the SW Indian Ocean heights. Anticyclonic circulations over Tropical Africa favour northerly anomalies that advect moisture over the region from the tropical Indian Ocean. Over West Africa, the MJO is responsible of recurrent dry conditions, alternating with a weak wet phase. The latter does not seem to result from deep convection only. The case of the East African Long Rains (March thr
Keywords: African Research